MENDORONG PERAN ORANG TUA DALAM MEMBANGUN LITERASI KEUANGAN ANAK SEJAK USIA DINI - Khairina Natsir (PROSIDING SERINA, 2021)
Financial literacy education with the target of early childhood is a concept to introduce how to manage finances wisely and sustainably in children from an early age so that children are skilled and able to control the use of money and are able to sort out what is a need and which is just a desire. Financial literacy in children can be built through the role of schools, families and the community. The partner is PMOG of Raudhatul Athfal Toufiqurahman Kindergarten which is located in Beji Timur Village, Depok. This school already has a financial education program for kindergarten students, namely the saving movement. Starting with saving education using traditional piggy banks. In the even semester of 2020-2021, the collaboration was continued with the saving movement at the BRI Agro Niaga bank Depok Branch. At that time the students opened a savings account at BRI. Teachers help collect data and documents needed for opening a savings account. BRI assisted in opening student accounts and collecting collective savings from schools. The PKM Tarumanagara University team contributed to encouraging the spirit of saving in children by providing an initial deposit of Rp. 220,000,- per child. The next challenge is how to motivate so that the amount of savings in children's accounts can continue to be increased and not decrease. In this case, the role of the family, especially parents, is very important in building children's financial literacy because most of the child's time is spent in the midst of the family and the family is the child's financial source.  In the odd semester of 2021-2022, the PKM activity is to provide counseling to parents of students to encourage develop the financial literacy in children from an early age. Community service activities were carried out with direct meetings at the Raudhatul Athfal Toufiqurahman Kindergarten school followed by parents of students in mid-November 2021. The activity was attended by 20 parents of students while still implementing health protocols.